Identification of Diseases and Pests of Cauliflower (Brassica oleracea) in the Pedan Hamlet Plantation, Karanglo, Tawangmangu - Fety Fatimah; Hidayatun Nurul Khasanah; Rif'atin Khoirunnisa; Farhah Qurrotu 'Aini; Nur Rokhimah Hanik (Jurnal Biologi Tropis, 2022)
Cauliflower (Brassicca oleracia var.brotrytis L.) is a type of vegetable that belongs to the Brassicaceae family (a type of cabbage with small white flowers). The purpose of the research on cauliflower (Brasica oleracea var. Botrytis L.) was to identify pests and diseases that attack cauliflower (Brasica oleracea var. Botrytis L.). The method used in this study was to go directly to the field once in August 2021. Observations were made on agricultural land owned by farmers in Pedan Hamlet, Karanglo Village, Tawangmangu, Karanganyar. The results showed that from three different land samples, different pests and diseases were encountered. In the first land sample, several pests were found such as grasshoppers, capers, spiders, and cauliflower caterpillars (Plutella xylostella) while the diseases that attacked were some cauliflower affected by whip tail disease, but very many cauliflower plants were found that were attacked by black rot and soft. In the second land sample, the most common pests found were capers, third field mop spiders, and the pests encountered were grasshoppers, spiders, capers and caterpillars and cauliflower caterpillars. While the disease that attacks is whiptail disease. In conclusion, the average pests that attack cauliflower plants are capers, spiders, cauliflower caterpillars and grasshoppers. And the common diseases that attack cauliflower plants are black rot, soft rot and whip tail.